2019
DOI: 10.1245/s10434-019-08100-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Primary Tumor Location in Synchronous Metastatic Colorectal Cancer: Differences in Metastatic Sites and Survival

Abstract: Purpose. We explored differences in survival between primary tumor locations, hereby focusing on the role of metastatic sites in synchronous metastatic colorectal cancer (mCRC). Methods. Data for patients diagnosed with synchronous mCRC between 1989 and 2014 were retrieved from the Netherlands Cancer registry. Relative survival and relative excess risks (RER) were analyzed by primary tumor location (right colon (RCC), left colon (LCC), and rectum). Metastatic sites were reported per primary tumor location. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 27 publications
8
46
0
3
Order By: Relevance
“…The superior survival for patients with left‐sided primary tumors compared to patients with right‐sided primary tumors is consistent with previous population based studies and clinical trials 52‐54 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The superior survival for patients with left‐sided primary tumors compared to patients with right‐sided primary tumors is consistent with previous population based studies and clinical trials 52‐54 …”
Section: Discussionsupporting
confidence: 88%
“…The superior survival for patients with left-sided primary tumors compared to patients with right-sided primary tumors is consistent with previous population based studies and clinical trials. [52][53][54] The strength of our study is the use of a registry containing high- There are some limitations to our study. First, only data from patients with synchronous metastatic disease were available for our study.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Several studies have shown that primary tumor location also is a prognostic factor in patients with (metastatic) colon cancer. [13][14][15][16] Colon tumors can be divided into left-sided and right-sided tumors. Right-and left-sided primary tumors differ in embryological origin (mid-gut vs hind-gut), bacterial flora and tumor biology (ie, mutational status and microsatellite instability (MSI)).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported an inferior outcome in right-sided colorectal tumours compared with left-sided tumours including rectal tumours [4,23,24], and this has been attributed to a more aggressive tumour biology and later diagnosis [23,25]. In this study, we chose to report on colon and rectal cancer separately because of the different clinical pathways.…”
Section: Discussionmentioning
confidence: 99%